The potential impact of nonsuicidal self-injury disorder: Insights from individuals with lived experience - Gregory J. Lengel; Brooke A. Ammerman; Keri-Anne Bell; Jason J. Washburn (Qualitative Research in Medicine & Healthcare, 2025)
Nonsuicidal self-injury disorder (NSSI-D) is presently a condition for further study in the Diagnostic & Statistical Manual of Mental Disorders (DSM-5-TR) (American Psychiatric Association, 2022). While previous studies focused on NSSI-D through the lens of experts, there is a shortage of research that explores the potential impact of NSSI-D from the perspective of those most directly affected - individuals with NSSI lived experience. The present study aimed to expand this limited literature and provide a more enhanced and nuanced understanding of the potential implications and consequences of NSSI-D from lived experience viewpoints. Adults with lifetime NSSI history (N = 38) completed a semi-structured interview that surveyed perspectives on NSSID, including the meaning of officially recognizing NSSI-D, potential impacts of receiving an NSSI-D diagnosis, and the impact of NSSI-D on one’s decision to speak with a clinician. Results from our thematic analysis of the interview data suggested opinions about NSSI-D and its potential impact were generally positive (e.g., increased awareness, understanding, and validation, increased comfort with disclosing NSSI behavior, positive impacts on treatment, and improved functioning). Participants also highlighted potential concerns about the potential consequences of NSSI-D (e.g., negative self-perception, increased stigma, and concerns about the necessity and utility of NSSI-D), and some expressed neutral/indifferent opinions about NSSI-D. Overall, results provide valuable insights regarding potential implications and consequences of official recognition and diagnosis of NSSID and have relevant implications for client-clinician interactions. Results also highlight the importance and value of amplifying lived experience perspectives.